Public preferences for preventative dental care: a discrete choice experiment in China - Dan Yang; Xiuxian Li; Bining Chen; Bixia Liu; Zhongcai Huang; Meirong Qin; Weiju Chen; Yonglan Tang; Xiaohong Wu; Jinsu Chen (Frontiers in Public Health, 2026)
Introduction The traditional treatment-oriented model is no longer sufficient to address the growing global burden of oral diseases. Although preventative oral health services effectively reduce the burden of oral diseases, their utilization remains suboptimal. Understanding the public preferences regarding preventative dental care (PDC) is essential to improve service efficiency and optimize preventative care programs. Methods A discrete choice experiment (DCE) questionnaire was distributed via face-to-face interviews to 277 participants recruited from three stomatology hospitals in South China. Six key attributes of PDC were identified. Mixed logit models were used to estimate the preferences for each attribute, while relative importance scores (RIS) and willingness-to-pay estimates (WTP) were calculated. Latent class analysis (LCA) was used to identify distinct preference patterns. Results Hospital type, risk of adverse reaction, service effectiveness, cost, attitude of provider, and care provider all significantly influenced respondents’ preferences. Hospital type was the most influential attribute. Respondents were willing to pay an additional RMB 1581.90 to upgrade from small private clinics to class A tertiary hospitals. Latent class analysis identified three distinct preference classes. Conclusion This study explores the PDC preferences of urban Chinese adults from demand-side perspective. Medical institutions should prioritize public preferences when redesigning PDC programs, thereby enhancing the acceptance rate of PDC.